Selectable Multiband Isolation Of Single Pole Double Throw Switch Using Transmission Line Stub Resonator For Wimax And Lte Applications - Abdullah Mohammed Saghir, Zobilah; Zahriladha, Zakaria; Noor Azwan, Shairi (Institution of Engineering and Technology, 2016)
This paper presents a selectable multiband isolation of Single Pole Double Throw (SPDT) switch with switchable transmission line stub resonators for applications of WiMAX and LTE in 2.3 and 3.5 GHz bands. Two SPDT switches are presented. (Design 2) either allows selecting only one band while unselecting the other or selecting both of them. However, (Design 1) does not allow so. The transmission line stub resonator used in this design is an open stub resonator with quarter wave of the electrical length. By using a simple mathematical model, the theory of the transmission line stub resonator was discussed where it can be cascaded and resonated at center frequencies of 2.3 and 3.5 GHz. Moreover, the cascaded transmission line stub resonators can be reconfigured between all-pass and band-stop responses using discrete PIN diodes. The key advantage of the proposed SPDT with switchable transmission line stub resonators is a multiband high isolation with a minimum number of PIN diodes. Therefore, the simulated and measured results showed the followings: less than 3 dB of insertion loss, greater than 10 dB of return loss and higher than 30 dB of multiband isolation in 2.3 and 3.5 GHz bands.